2023
DOI: 10.1186/s13568-023-01546-7
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional role of some biogenic nanoparticles in controlling wilt disease and promoting growth of common bean

Abstract: In the present era, nanomaterials are emerging as a powerful tool for management of plant disease and improving crop production to meet the growing global need for food. Thus, this paper was conducted to explore the effectiveness of five different types of nanoparticles (NPs) viz., Co3O4NPs, CuONPs, Fe3O4NPs, NiONPs, and ZnONPs as treatments for Fusarium wilt as well as their role in promoting growth of the common bean plant. The five types of NPs were applied as a treatment for wilt in two ways, therapeutic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…A previous study also demonstrated that the combined application of CuONPs and Bacillus subtilis could enhance growth parameters in wheat, including root length, stem length, and biomass (Haider et al 2023). Recently, a study also showed that CuONPs could promote the growth of nutrients (El-Sayed et al 2023). Another study found that CuONPs were effective under greenhouse conditions, which could reduce disease incidence and increase biomass and yield (Elmer et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study also demonstrated that the combined application of CuONPs and Bacillus subtilis could enhance growth parameters in wheat, including root length, stem length, and biomass (Haider et al 2023). Recently, a study also showed that CuONPs could promote the growth of nutrients (El-Sayed et al 2023). Another study found that CuONPs were effective under greenhouse conditions, which could reduce disease incidence and increase biomass and yield (Elmer et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…HA also positively affects the nutrient absorption of plants and is particularly important for the transport and the availability of micronutrients (Sharif et al, 2002;El-Sayed et al, 2023).Various studies manifested that the treatment with HA led to an improvement in the growth characteristics of the plant as the same in Passiflora edulis (Cavalcante et al, 2013), Achilleamille folium (Bayat et al, 2021), and garden cress (Yildirim et al, 2021).…”
Section: Iron Content (Ppm)mentioning
confidence: 99%
“…The applicability of the NPs has been greatly enhanced by their reduced size, special physicochemical features, and surface changes (Hussein et al 2022 ). Among metal oxide nanoparticles, ZnO-NPs are widely employed in biomedical uses such as drug delivery, antibacterial, anticancer, antioxidant, and wound healing (Gomaa et al 2022 ). Zinc is a neuromodulator that carries out a variety of physiological actions (Blakemore and Trombley 2017 ; Hatab et al 2022 ), and it is vital for controlling cell proliferation.…”
Section: Introductionmentioning
confidence: 99%